Selegiline remarkably improved stage 5 treatment-resistant major depressive disorder: a case report - Kitaichi Y (Dove Medical Press, 2013)
Yuji Kitaichi,1 Takeshi Inoue,1 Nobuyuki Mitsui,1 Shin Nakagawa,1 Rie Kameyama,1 Yoshiyuki Hayashishita,1 Tohru Shiga,2 Ichiro Kusumi,1 Tsukasa Koyama1 1Department of Psychiatry, Graduate School of Medicine, Hokkaido University, Sapporo, Japan; 2Department of Nuclear Medicine, Graduate School of Medicine, Hokkaido University, Sapporo, Japan Abstract: We report a case in which selegiline, an irreversible monoamine oxidase B (MAO-B) inhibitor, greatly improved depressive symptoms in an adult with stage 5 treatment-resistant major depressive disorder. Four antidepressants and four augmentation therapies had previously been ineffective or intolerable, and electroconvulsive therapy had only a temporary effect. After 20 weeks of treatment with selegiline (10 mg/day), the patient's score on the 17-item Hamilton Depression Rating Scale (HDRS) had decreased from 19 to 4 points. [18F]-Fluorodeoxyglucose positron emission tomography (FDG-PET) showed increased glucose metabolism in the bilateral basal ganglia after initiating selegiline treatment; blood dopamine levels were also increased after selegiline treatment. These results raise the possibility that selegiline enhances dopaminergic neural transmission in treatment-resistant depression, thus leading to an improvement in depressive symptoms. Keywords: treatment-resistant depression, FDG-PET, glucose metabolism, basal ganglia